A DSP Based Optimal Algorithm for Shunt Active Filter Under Nonsinusoidal Supply and Unbalanced Load Conditions - George, S.; Agarwal, V. (IEEE transactions on power electronics, 2007)
The use of power electronic circuits in a wide range of applications has resulted in distorted current waveforms in the power system. This results in nonsinusoidal voltage drops across the transformers and transmission line impedances, resulting in a nonsinusoidal voltage supply at the point of common coupling. Asymmetrical distribution of large, 1-phi loads further complicates the issue by causing imbalance in the line currents of the 3-phi system. Not only should this imbalance be compensated, other parameters, such as the current total harmonic distortion and the power factor should also be maintained as per the norms. However, the requirements of harmonic free current waveforms and good power factor, under nonsinusoidal voltage conditions, are contradictory to each other. Under these conditions, an optimum performance is the best one can achieve. This paper proposes a new scheme for balancing the currents and obtaining the best compromise between the power factor and current distortion under nonsinusoidal voltage conditions. The technique does not use p-q theory and does not require sequence transformation for power calculations, even though the current is unbalanced. All the details of this work are presented